Towards 'Engagement 2.0': Insights from a study of dynamic consent with biobank participants - Teare, H; Morrison, M; Whitley, E; Kaye, J (SAGE Publications, 2015)
Web 2.0 technologies have enabled new methods of engagement, moving from static mono-directional sources of information to interactive user-led experiences. Use of Web 2.0 technologies for engagement is gaining momentum within the health sector however this is still in its infancy in biobanking research. This paper reports on findings from focus groups with biobank participants to gauge their views on a Web 2.0 dynamic consent interface. The findings from this study suggest that participants would welcome more interactive engagement with biobanks, and the opportunity to hear more about how their data and samples are being used in research. We propose that by adopting Web 2.0 tools for dynamic consent, we can move towards an ‘Engagement 2.0’ model whereby research participants have the opportunity for more interactive engagement with medical research, setting up a two-way communication channel between participants and researchers, for the benefit of both.